Antropomorfisme Yahudi Dalam Al-Qur’an (Kajian Tafsir Klasik dan Modern) - Ramadani, Bayu Rindy; Muttaqein, Ahmad; Masruchin, Masruchin (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
AbstractThis research seeks to interpret the verses that show the attitude anthropomorphism towards God. Because Jews are the most fiercely opposed to Islam and have a great hostility toward Islam, this study tries to understand the verses that reflect the attitude of Jewish anthropomorphism towards God. The library research method was combined with the Maudhu'i methodology in this study. Researcher employs content-analysis techniques to get a valid conclusion based on the object of study. As a result of this research, Jews believe Allah is a God who is stingy and parsimonious since Allah's hands are bound, so that can conclude from this study that when we come across verses like this, not not interpret them the way Jews do. But must communicate its latent meaning through diverse interpretation methods so its explicit meaning does not stick to usKeywords: Anthropomorphism; Attitude; Yahudi. AbstrakPenelitian ini bertujuan untuk meinterpretasikan ayat-ayat yang menunjukkan sikap antropomorfisme Yahudi terhadap Allah. Sebab Yahudi adalah yang paling keras menentang Islam dan kental permusuhannya dengan Islam. Penelitian ini menggunakan metode library research dengan pendekatan maudhu’i. Peneliti menggunakan teknik content-analys untuk dapat menarik suatu kesimpulan yang valid berdasarkan objek kajian. Hasil dari penelitian ini ialah kalangan Yahudi berasumsi bahwa Allah adalah Tuhan yang kikir, pelit, sebab tangan Allah telah terbelenggu, sehingga dapat disimpulkan bahwa tatkala bertemu dengan ayat-ayat seperti ini, jangan memahaminya sebagaimana kalangan Yahudi memahami. Akan tetapi harus mengungkapkan makna implisitnya dengan berbagai metode tafsir, sehingga kita tidak terjebak kedalam makna eksplisitnya. Kata Kunci: Antropomorfisme; Sikap; Yahudi.